The Prosomia of the Eight Modes According to Dimitrie Cunțanu - MOCANU, Daniel (Studia Universitatis Babes-Bolyai Musica, 2025)
The aim of the present study is to analyse the prosomia recorded in the ecclesiastical musical tradition of Transylvanian, based on the collection of „Cântări bisericești” (Church Hymns), published by Dimitrie Cunțanu in 1890 in Vienna. The collection represents a significant attempt to standardize the Orthodox liturgical singing of the Metropolis of Transylvania, aligning itself with similar efforts previously undertaken in Wallachia and Moldova. By means of a historical-musicological research method, the present study highlights the context of the emergence of these melodic variants, the characteristics of the included prosomia, as well as their impact on contemporary musical practice. Prosomia, introduced as melodic interpretation models for hymns lacking their own musical line, constitute a point of intersection between the Byzantine tradition and the influences of Transylvanian folk music. The research reveals the presence of varied modal structures, including diatonic and chromatic modes, with a limited ambitus, a predominance of syllabic rhythm, and modal adaptations specific to the Transylvanian cultural-religious context. These features initially facilitated the integration of the prosomia into the musical repertoire but were later affected by the lack of continuity in the musical training of church singers and the preference for oral transmission of the hymns. In this context, the analysis of cadential formulas and modal particularities highlights an attempt to harmonize the Byzantine tradition with the musical and social realities of the Orthodox communities in Transylvania. The study highlights the fact that, despite their historical and pedagogical importance, Cunțanu’s prosomia have been gradually marginalized, being preserved only in a few parishes in southern Transylvania. The causes of this decline in visibility can be attributed to the lack of specialized singers, the formulaic structures, and melodic lines, distinct from the traditional system of the eight ecclesiastical modes. Additionally, the lack of interest in institutional frameworks to support the continuity of the tradition of prosomia and the preference for adapting hymn texts to the melodic structures of the resurrection troparia contributed to their diminishing role. The present study provides a detailed insight into the process of adapting the Byzantine musical tradition in Transylvanian space and the dynamics between orality, local cultural influences, and efforts to standardize prosomia. The conclusions provide a basis for future research on the mechanisms of adaptation and transformation of ecclesiastical singing and contribute to the understanding of the evolutionary dynamics of liturgical music in Transylvania, as well as the potential for revitalization of this musical heritage with identity and cultural value.